Interferon-γ-Directed Inhibition of a Novel High-Pathogenic Phlebovirus and Viral Antagonism of the Antiviral Signaling by Targeting STAT1 - Ning, Yun-Jia; Mo, Qiong; Feng, Kuan; Min, Yuan-Qin; Li, Mingyue; Hou, Dianhai; Peng, Cheng; Zheng, Xin; Deng, Fei; Hu, Zhihong; Wang, Hualin (Frontiers in Immunology, 2019)
Severe fever with thrombocytopenia syndrome (SFTS) is a life-threatening infectious disease caused by a novel phlebovirus, SFTS virus (SFTSV). Currently, there is no vaccine or antiviral available and the viral pathogenesis remains largely unknown. In this study, we demonstrated that SFTSV infection results in substantial production of serum interferon- (IFN-) in patients and then that IFN- in turn exhibits a robust anti-SFTSV activity in cultured cells, indicating the potential role of IFN- in anti-SFTSV immune responses. However, the IFN- anti-SFTSV efficacy was compromised once viral infection had been established. Consistently, we found that viral nonstructural protein (NSs) expression counteracts IFN- signaling. By protein interaction analyses combined with mass spectrometry, we identified the transcription factor of IFN- signaling pathway, STAT1, as the cellular target of SFTSV for IFN- antagonism. Mechanistically, SFTSV blocks IFN--triggered STAT1 action through 1) NSs-STAT1 interaction-mediated sequestration of STAT1 into viral inclusion bodies and 2) viral infection-induced downregulation of STAT1 protein level. Finally, the efficacy of IFN- as an anti-SFTSV drug in vivo was evaluated in a mouse infection model: IFN- pretreatment but not posttreatment conferred significant protection to mice against lethal SFTSV infection, confirming IFN-’s anti-SFTSV effect and viral antagonism against IFN- after the infection establishment. These findings present a picture of virus-host arm race and may promote not only the understanding of virus-host interactions and viral pathogenesis but also the development of antiviral therapeutics.